Performance analysis of constant current heated antagonistic shape memory alloy actuator using a differential resistance measurement technique. (12th November 2021) - Bhargaw, Hari N; Botre, B A; Singh, Samarth; Hashmi, S A R; Akbar, S A; Sinha, Poonam
Abstract: This work presents the development of a precise, constant current heating mechanism for an antagonistic shape memory alloy (SMA) actuator. The actuator was developed using a pair of SMA wires arranged in an antagonistic configuration. SMA possesses a unique phase-dependent, resistance variation property which is called self-sensing. This phenomenon is observed during thermal phase transition. A constant heating current was employed to measure combined differential resistance (Δ R ) which provides insignificant hysteresis and linear relationship with displacement. Δ R eventually helps to determine the present position of the actuator for sensorless feedback control. The aim is to remove additional external sensors, reducing actuator footprint and interface complexity using the proposed study. The performance analysis of the actuator was evaluated under constant current by the tracking trajectory of reference signals. The tracking results confirmed the improvement in operating bandwidth by a reduction in displacement. The heating module mainly consisted of a low pass filter, operational amplifier with a current sense feedback mechanism that regulates the heating current in proportion to PWM signals. The result shows a significant 21% variation in the observed value of Δ R (1.200–0.254 Ω) between the major–minor loops. The study confirms linearity and maintains similarity by highest correlation 0.9508 during open-loop, which further improves to 0.9891 in close feedback reference tracking with an error band ±0.05 mm.